Feasibility of Conventional Biotechnology Practicum Guide Based on Physics, Chemistry, and Organoleptic Test Results of Cincalok - Audiva Azhta Prameswari; Laili Fitri Yeni; Anisyah Yuniarti (Al Jahiz, 2026)
The practicum guide is a guideline for conducting practicum activities. Cincalok was chosen as the practicum guide because of its closeness to the local wisdom of the students, so that the concept of conventional biotechnology can be understood contextually. The use of locally-based fermented products supports relevant learning, and strengthens students' appreciation of local culture and food resources. This study aims to analyze the feasibility of teaching materials for practical guides on conventional biotechnology sub-material regarding the results of physical, chemical, and organoleptic tests of cincalok in West Kalimantan. The research design used was quantitative descriptive. The feasibility test was conducted in three stages, namely instrument validation, media validation, and data analysis. The validators consisted of five people, namely two lecturers from the Biology Education Study Program and three biology teachers from grade X high school. The validation results obtained a CVR value of 0.99 and a CVI value of 0.99, indicating that all aspects of the practical guide assessment were valid. This shows that the practical guide that was created met the criteria in terms of format, language, and content. The practical guide that met the validity criteria could be used in the next stage to evaluate its effectiveness.